Pelaksanaan Penguatan Pengawasan Internal Dalam Penyelenggaraan Reformasi Birokrasi Di Balai Pelatihan Lingkungan Hidup Dan Kehutanan (BPLHK) Samarinda - Septianti, Dina; Mega, Mega; Dewi R, Khairunisa Putri; Natalia, Feodora; Shidiq Q, Hasbie; Syandana, Salsabila; Paselle, Enos (Saraq Opat: Jurnal Administrasi Publik, 2024)
Bureaucracy plays a major role in the process of providing public services. However, in the implementation of public services, various bureaucratic problems are still encountered. So bureaucratic reform is needed as a start to formulating a good, effective and efficient government administration system, so that it can serve the public quickly, precisely and professionally. In addition, government agencies and their leaders and staff must be committed to realizing a Corruption-Free Area/Clean and Serving Bureaucratic Area through bureaucratic reform, especially in realizing clean and accountable government and excellent public services as stated in Permenpan RB Number 90 of the Year 2021. This research aims to determine the Implementation of Strengthening Internal Supervision in Implementing Bureaucratic Reform at the Samarinda Environmental and Forestry Training Center. The method used in this research is descriptive qualitative. With the result that BPLHK has implemented strengthened supervision and fulfilled indicators based on PERMENPAN RB RI Number 26 of 2020 concerning Gratification Control in the Ministry of Environment and Forestry, which includes Gratification, Implementation of SPIP, Public Complaints, Whistle-blowing system, Handling of conflicts of interest, Development integrity zone, and the Government Internal Monitoring Apparatus (APIP) but there are still obstacles to achieving WBK/WBBM.